Analisis Karya Kolase Tema Amfibi Menggunakan Bahan Origami Karya Siswa Kelas XI IPS Sekolah SMAS Budi Satrya T.A 2024/2025 - Raja Kores Galatia Sitorus; Nelson Tarigan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the results of collage work by applying collage on plywood media using origami reviewed from the